2015
DOI: 10.11648/j.plant.20150306.11
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Spectroscopic Characterization of Biofield Energy Treated Gerbera Multiplication Medium

Abstract: Abstract:The micropropagation technique is used for Gerbera species due to their high demand all over the world as the decorative potted plants and cut flowers. The present study was done to investigate the impact of biofield energy treatment on the physicochemical properties of gerbera multiplication medium. A part of the sample was treated with Mr. Trivedi's biofield energy, and the other part was kept as untreated and termed as the control sample. Both the parts were subsequently analysed for their physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The National Center of Complementary and Integrative Health (NCCIH) has recognized and accepted Biofield Energy Healing as a complementary and alternative medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [16]. From the study on the various fields include materials science [17,18], pharmaceuticals [19,20], nutraceuticals [21,22], organic compounds [23][24][25], microbiology [26][27][28], agricultural [29,30], biotechnology [31][32][33], genetics [34,35], it has been proven that Biofield Energy Healing (also known as The Trivedi Effect ® ) has the astounding capability for alteration of the characteristic properties of the several non-living materials and living organisms. From the scientific literature, it has been found that the bioavailability of inorganic selenium is lower than the organic forms of selenium such as selenium methionine.…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has recognized and accepted Biofield Energy Healing as a complementary and alternative medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [16]. From the study on the various fields include materials science [17,18], pharmaceuticals [19,20], nutraceuticals [21,22], organic compounds [23][24][25], microbiology [26][27][28], agricultural [29,30], biotechnology [31][32][33], genetics [34,35], it has been proven that Biofield Energy Healing (also known as The Trivedi Effect ® ) has the astounding capability for alteration of the characteristic properties of the several non-living materials and living organisms. From the scientific literature, it has been found that the bioavailability of inorganic selenium is lower than the organic forms of selenium such as selenium methionine.…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has recognized and accepted Biofield Energy Healing as a complementary and alternative medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [16]. Scientific study on the various fields such as materials science [17][18][19], pharmaceuticals [20][21][22], nutraceuticals [23,24], organic compounds [25][26][27], microbiology [28][29][30], agricultural [31,32], biotechnology [33][34][35], genetics [36,37], medical sciences [38,39], has been proven that Biofield Energy Healing (The Trivedi Effect ® ) has the astounding capability for the alteration of the characteristic properties of the living and non-living substances. Scientific literature reported that the bioavailability of inorganic selenium is lower than the organic forms of selenium such as selenium methionine.…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [16]. From the study on the various fields include materials science [17,18], organic compounds [19][20][21], nutraceuticals [22,23], pharmaceuticals [24,25], microbiology [26][27][28], agricultural [29,30], biotechnology [31][32][33], genetics [34,35], it has been proven that Biofield Energy Healing (also known as The Trivedi Effect ® ) has the astounding capability for alteration of the characteristic properties of the several non-living materials and living organisms. From the scientific literature, it has been found that the bioavailability of inorganic selenium is lower than the organic forms of selenium such as selenium methionine.…”
Section: Introductionmentioning
confidence: 99%